Aortic Anatomic Severity Grade Correlates with Midterm Mortality in Patients Undergoing Abdominal Aortic Aneurysm Repair. (May 2019) - Young, Zane Z.; Balceniuk, Mark D.; Rasheed, Khurram; Mix, Doran; Esce, Antoinette; Ellis, Jennifer L.; Glocker, Roan J.; Doyle, Adam J.; Raman, Kathleen; Stoner, Michael C.
Background: Anatomic severity grade (ASG) can be used to assess abdominal aortic aneurysm (AAA) anatomic complexity. High ASG is associated with complications following endovascular repair of AAAs and we have demonstrated that ASG correlates with resource utilization. The hypothesis of this study is that ASG is directly related to midterm mortality in patients undergoing AAA repair. Methods: Patients who underwent infrarenal AAA repairs between July 2007 and August 2014 were retrospectively reviewed and ASG scores were calculated using 3-dimensional computed tomography reconstructions. Perioperative mortalities (≤30 days) were excluded. The ASG value of 15 was chosen based on previous receiver–operator curve analysis, which showed that an ASG of 15 was predictive of postoperative complications and resource utilization. The 5-year survivors and mortalities were compared utilizing comorbidities, pharmacologic variables, and anatomic variables at or above the defined threshold. Results: A total of 402 patients (80% male and 96% Caucasian) with complete anatomic and survival data were included in the analysis. Mean ASG and age at the time of repair were 16 ± 0.15 and 73 ± 0.43 years old, respectively. The 5-year mortality was significantly associated with ASG >15 (hazard ratio [HR]: 1.504, confidence interval [CI]: 1.077-2.100, P < .017), hyperlipidemia (HR: 1.987, CI: 1.341-2.946, P < .001), coronary artery disease (HR: 1.432, CI: 1.037-1.978, P < .029), and chronic obstructive pulmonary disease (HR: 1.412, CI: 1.027-1.943, P < .034). Kaplan-Meier analysis demonstrated improved survival in the low score ASG ≤15 group at 1, 3, and 5 years (96% vs 93%, 81% vs 69%, and 53% vs 41%; P = .0182; Figure 1). Conclusions: Increasing aortic anatomic complexity as characterized by ASG >15 is an independent predictor of midterm mortality following elective infrarenal AAA repair. Therefore, it may be a useful tool for appropriate patient selection and risk stratification prior to elective infrarenal AAA repair.